2017
DOI: 10.1177/0954407017735383
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of bore/stroke ratio and scavenge port angles on the scavenging process in a two-stroke boosted uniflow scavenged direct injection gasoline engine

Abstract: In this study, a two-stroke boosted uniflow scavenged direct injection gasoline (BUSDIG) engine was proposed and researched to achieve aggressive engine downsizing and downspeeding. Compared to loop or cross scavenged twostroke engines, the BUSDIG engine can achieve excellent scavenging performance and be operated with higher boost pressure as well as the absence of air and fuel short-circuiting. As a fundamental engine geometric parameter, the bore/ stroke (B/S) ratio would directly affect the scavenging proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The centrally mounted DI injector and spark plug on the cylinder head were positioned to place the spray recirculation region around the spark plug. The key engine design parameters, including engine bore/stroke ratio, 39 scavenge port angles, 4042 opening profiles of scavenge ports and exhaust valves 43 and intake plenum, 44 have been analysed and evaluated for optimal scavenging performance and in-cylinder flow motions. A full review of the BUSDIG engine concept can be found in a recently published article.…”
Section: Specifications Of the Two-stroke Busdig Enginementioning
confidence: 99%
“…The centrally mounted DI injector and spark plug on the cylinder head were positioned to place the spray recirculation region around the spark plug. The key engine design parameters, including engine bore/stroke ratio, 39 scavenge port angles, 4042 opening profiles of scavenge ports and exhaust valves 43 and intake plenum, 44 have been analysed and evaluated for optimal scavenging performance and in-cylinder flow motions. A full review of the BUSDIG engine concept can be found in a recently published article.…”
Section: Specifications Of the Two-stroke Busdig Enginementioning
confidence: 99%
“…In light of the advantages of the 2-stroke operation, a novel 2-stroke Boosted Uniflow Scavenged Direct Injection Gasoline (BUSDIG) engine has been designed and extensively researched at Brunel since 2015 [7]. Key designs of the proposed BUSDIG engine, including engine bore/stroke ratio [8], scavenge ports [9][10][11], opening profiles of scavenge ports and exhaust valves [12], intake plenum [13], injection strategies [14,15] and piston shape [16] have been systematically studied to optimise the scavenging performance and charge preparation of the BUSDIG engine.…”
Section: Introductionmentioning
confidence: 99%